2011
DOI: 10.1177/0022429410396094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Listening Conditions, Error Types, and Ensemble Textures on Error Detection Skills

Abstract: This study was designed with three main purposes: (a) to investigate the effects of two listening conditions on error detection accuracy, (b) to compare error detection responses for rhythm errors and pitch errors, and (c) to examine the influences of texture on error detection accuracy. Undergraduate music education students (N = 18) listened to purposefully incorrect performances of band literature in two formats, on recordings and while conducting a live ensemble. Pitch and rhythm errors were inserted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 13 publications
2
34
0
3
Order By: Relevance
“…Of course, a teacher needs to address errors while they are teaching on the podium and not merely in listening contexts. In an effort to bring more ecological validity to the task of error detection, Waggoner (2011) asked instrumental majors to detect errors in full band and sectional settings, both while conducting an ensemble and while simply listening to a recording. Candidates were more successful at identifying errors when just listening.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Of course, a teacher needs to address errors while they are teaching on the podium and not merely in listening contexts. In an effort to bring more ecological validity to the task of error detection, Waggoner (2011) asked instrumental majors to detect errors in full band and sectional settings, both while conducting an ensemble and while simply listening to a recording. Candidates were more successful at identifying errors when just listening.…”
Section: Related Literaturementioning
confidence: 99%
“…While recordings allow for controlled stimuli and more efficient testing, they compromise ecological validity for the task teachers actually do. Future studies should continue to examine error detection in both recorded and live-listening contexts (Waggoner, 2011).…”
Section: Limitationsmentioning
confidence: 99%
“…Error detection (a teacher’s or conductor’s ability to identify errors in performance) is one of those critical, complex tasks (Sheldon, 2004). Waggoner (2011) suggested that understanding how specific factors affect error detection skill may lead to the development of more effective curricula. Interval perception and error detection have long histories of study in music education and music cognition research, yet researchers have only included them within the same empirical design in general ways.…”
mentioning
confidence: 99%
“…2008), match pitch accurately (e.g., Demorest & Clements, 2007), take dictation efficiently (Buonviri, 2014;Potter, 1990), conduct effectively (e.g., Waggoner, 2011), compose original tunes (e.g., Kennedy, 2002), and learn to improvise (e.g., Hickey, 2009). Therefore, the ways students acquire and use listening skills may strongly influence their overall development as musicians.…”
mentioning
confidence: 99%
“…Research has shown that seemingly complementary musical tasks may detract from focused listening. Waggoner (2011) discovered that undergraduate music majors were less adept at error detection when conducting a piece than when listening to a recording of it. She concluded that their attention to conducting may have inhibited their attention to listening.…”
mentioning
confidence: 99%